2009
DOI: 10.1523/jneurosci.0740-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

The Central Nucleus of the Amygdala and Corticotropin-Releasing Factor: Insights into Contextual Fear Memory

Abstract: The central nucleus of the amygdala (CeA) has been traditionally viewed in fear conditioning to serve as an output neural center that transfers conditioned information formed in the basolateral amygdala to brain structures that generate emotional responses. Recent studies suggest that the CeA may also be involved in fear memory consolidation. In addition, corticotropin-releasing factor systems were shown to facilitate memory consolidation in the amygdala, which contains a high density of CRF immunoreactive cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 65 publications
7
63
0
Order By: Relevance
“…Functionally, the central nucleus is involved in mediating the behavioral and physiological responses associated with fear and anxiety, it modulates hormonal responses to stress and plays an important role in learning Pavlovian conditioning (Kalin et al, 2004;Liubashina et al, 2000). It has recently been proposed, that while the central nucleus of the amygdala is involved in acute fear responses, the bed nucleus of the stria terminalis is more related to anxiety responses (Pitts et al, 2009). The lateral bed nucleus of the stria terminalis is a heterogeneous cell continuum expanding from the internal capsule on the medial side to the nucleus accumbens rostrally, it borders the caudate nucleus dorsally and reaches the IPAC at its caudal end.…”
Section: The Extended Amygdalamentioning
confidence: 99%
“…Functionally, the central nucleus is involved in mediating the behavioral and physiological responses associated with fear and anxiety, it modulates hormonal responses to stress and plays an important role in learning Pavlovian conditioning (Kalin et al, 2004;Liubashina et al, 2000). It has recently been proposed, that while the central nucleus of the amygdala is involved in acute fear responses, the bed nucleus of the stria terminalis is more related to anxiety responses (Pitts et al, 2009). The lateral bed nucleus of the stria terminalis is a heterogeneous cell continuum expanding from the internal capsule on the medial side to the nucleus accumbens rostrally, it borders the caudate nucleus dorsally and reaches the IPAC at its caudal end.…”
Section: The Extended Amygdalamentioning
confidence: 99%
“…On the other hand, several studies provide evidence for a role of CRF in contextual conditioning (Deak, Nguyen, Ehrlich, Watkins, Spencer, Maier et al, 1999;Hubbard, Nakashima, Lee, & Takahashi, 2007;Ohmura, Yamaguchi, Izumi, Matsumoto, & Yoshioka, 2008;Pitts, Todorovic, Blank, & Takahashi, 2009). To clarify this apparent discrepancy between GAD and CC, further CRF studies in patients are needed.…”
Section: Face Validitymentioning
confidence: 99%
“…In fact, other studies have found that CeA infusion of a CRF antagonist prior to contextual fear conditioning (Swiergiel et al, 1993) or CRF antisense at different time points after contextual fear conditioning (Pitts et al, 2009; Pitts and Takahashi, 2011) is effective at modulating fear memory. The lack of effectiveness of CRF receptor antagonists in the CeA in some studies may be partially explained by the relative expression of CRF receptors in the BLA compared to the CeA.…”
Section: Introductionmentioning
confidence: 99%